Justiciability of Economic, Social, and Cultural Rights: The UN Committee on Economic, Social and Cultural Rights’ Review of China’s First Periodic Report on the Implementation of the International Covenant on Economic, Social and Cultural Rights - Choukroune, Leila (Columbia Journal of Asian Law, 2005)
One of the most debated issues surrounding State parties’ implementation of their obligations under the International Covenant on Economic, Social and Cultural Rights (the “ICESCR” or “the Covenant”) is the possibility for aggrieved citizens-including particularly vulnerable or disadvantaged ones-to seek redress for violations of their rights under the Covenant. All State parties are not only required to implement the Covenant on a non-discriminatory basis, but are also obligated to give effect to the ICESCR in their domestic legal order by using “all appropriate means, including legislative measures” to achieve “progressively the full realization of the rights recognized.” Thus, in its General Comment n’9 (1998), on the domestic application of the Covenant, the UN Committee on Economic, Social and Cultural Rights considered that “appropriate means of redress, or remedies, must be available to any aggrieved individual or group, and appropriate means of ensuring governmental accountability must be put in place.” Justiciability, defined as the possibility for domestic courts to “take account of Covenant rights where this is necessary to ensure that the State’s conduct is consistent with its obligations under the Covenant,” could serve as a good indicator for assessing State party compliance with the ICESCR while evaluating the degree of independence and professionalism of local judiciaries necessary for progressive realization of the rule of law.